Schaum's outline of theory and problems of college chemistry - Rosenberg, Jerome L. (New York : McGraw Hill Education, 1990)
This book is designed to help the student college chemistry by summarizing the chemical principles of each topic and relating the solution of quantitative problems to those fundamentals.